2008
DOI: 10.1051/ebr:2008021
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of viable row-crop seeds of commercial agriculture by farmland birds: implication for genetically modified crops

Abstract: To address some concerns about the expansion of genetically engineered pharmaceutical and industrial crops to outdoor plantings and potential impacts on the human food supply, we determined whether commercial agriculture seeds of maize or corn Zea mays L., barley Hordeum vulgare L., safflower Carthamus tinctorius L. and rice Oryza sativa L. are digested or pass viably through the digestive tract, or are transported externally, by captive mallard ducks Anas platyrhynchos L., ring-necked pheasants Phasianus colc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…When it was not possible to assign a morphotype to species level with certainty, genus or family level was reported. We did not include rice grains (Oryza sativa) as seeds dispersed because they were unlikely to be viable (Cummings et al, 2008…”
Section: Sample Processingmentioning
confidence: 99%
“…When it was not possible to assign a morphotype to species level with certainty, genus or family level was reported. We did not include rice grains (Oryza sativa) as seeds dispersed because they were unlikely to be viable (Cummings et al, 2008…”
Section: Sample Processingmentioning
confidence: 99%
“…For some larger animals such as cattle, foraging or grazing is minimal due to the spiny nature of mature safflower plants (Cummings et al, 2008) but sheep and goats are not irritated by the spines. Feral pigs or boars are destructive and difficult to exclude from fields (Rao et al, 2015).…”
Section: Animalsmentioning
confidence: 99%
“…Safflower seed dispersal by several bird species (blackbirds, mallard ducks, pigeons and pheasants) was examined and it was observed that seed did not pass through the digestive tract but did remain viable in the oesophagus and gizzard regions for several hours. The safflower seed viability was measured as a percentage of germination, where the germination rate was in the range of 16-30% and 4-29% for seed collected from the oesophagus and gizzards of birds respectively (Cummings et al, 2008). A few seeds were also transported externally on soil attached to feet or legs of pheasants and pigeons (Cummings et al, 2008;Vazačová and Münzbergová, 2013).…”
Section: Animalsmentioning
confidence: 99%
“…Winter flooding not only enhances degradation of seeds on the soil surface (Fogliatto et al 2011;Singh et al 2016a) but also attracts birds and encourages predation of freshly deposited rice (weedy or not) seeds. Intact rice seeds are not passed through the feces of ducks, and there is little chance of birds spreading viable rice seeds (Cummings et al 2008). Thus, winter flooding is an effective cultural strategy to reduce a weedy rice infestation.…”
Section: Overview Of Rice Farmingmentioning
confidence: 99%